2012
DOI: 10.3389/fimmu.2012.00294
|View full text |Cite
|
Sign up to set email alerts
|

The Yin and Yang of Human Beta-Defensins in Health and Disease

Abstract: Rapidly evolving research examining the extended role of human beta-defensins (hBDs) in chemoattraction, innate immune-mediated response, and promotion of angiogenesis suggest that the collective effects of hBDs extend well beyond their antimicrobial mechanism(s). Indeed, the numerous basic cellular functions associated with hBDs demonstrate that these peptides have dual impact on health, as they may be advantageous under certain conditions, but potentially detrimental in others. The consequences of these func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
54
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 93 publications
(144 reference statements)
2
54
0
1
Order By: Relevance
“…13 Based on Figure 2, the results of immunohistochemical examination for BD-2 expressions in the gingival epithelium showed that BD-2 is expressed in stratum spinosum and stratum granulosum. The results is in line with the results of a research conducted by Weinberg et al, 14 stating that within the gingival tissue, mRNA from SW-1 and SW-2 is located in the suprabasal stratified epithelium, while peptide BD-2 is detected in the upper epithelial layers. 15 Gingiva, hard palate, and the dorsal part of the tongue is the keratinized epithelium of the oral cavity, while the floor of the mouth and the buccal area are not keratinized epithelium.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…13 Based on Figure 2, the results of immunohistochemical examination for BD-2 expressions in the gingival epithelium showed that BD-2 is expressed in stratum spinosum and stratum granulosum. The results is in line with the results of a research conducted by Weinberg et al, 14 stating that within the gingival tissue, mRNA from SW-1 and SW-2 is located in the suprabasal stratified epithelium, while peptide BD-2 is detected in the upper epithelial layers. 15 Gingiva, hard palate, and the dorsal part of the tongue is the keratinized epithelium of the oral cavity, while the floor of the mouth and the buccal area are not keratinized epithelium.…”
Section: Discussionsupporting
confidence: 82%
“…This situation suggests that keratinization in the epithelium of the oral cavity plays an important role for the retention of peptides. 14 The results found in the negative control group in this research can be associated to the results found in normal epithelium condition as stated by Abiko Y et al since the group was not treated. BD-2 expressions in the gingival epithelium in the negative control group were 15.80, while BD-2 expressions in the treatment group 1were 24.00, and 127.00 in the treatment group 2 ( Table 1).…”
Section: Discussionsupporting
confidence: 74%
“…Based on all available reports, while for activating the innate immune system and preventing deleterious effects on infections, both activities should be positively viewed, it is unlikely that HDP will end up in the treatment arsenal against rheumatoid arthritis or other inflammatory diseases, as single experiments would suggest. In fact, similar observations were made on human β-defensins, as the basic cellular functions associated with these HDPs demonstrate dual impact on health that might be advantageous under certain conditions and detrimental in others [110]. No doubt HDP will end up on pharmacy shelves [111] …”
Section: Discussionmentioning
confidence: 60%
“…This, along with other results showing that hBD-2 is induced as a result of inflammation via MAPK or NF〉 (5) while hBD-3 is activated through epidermal growth factor receptor (13, 14), strongly suggests that the latter is more involved in wound healing while the former plays a more active role in inhibiting microbial invasion during mucosal-barrier disruption (15-17). Moreover, in addition to their antimicrobial properties (18, 19), both peptides have been shown to act as chemokines in recruiting lymphoid and myeloid cells from the bloodstream (20).…”
mentioning
confidence: 99%
“…This, along with other results showing that hBD-2 is induced as a result of inflammation via MAPK or NF〉 (5) while hBD-3 is activated through epidermal growth factor receptor (13, 14), strongly suggests that the latter is more involved in wound healing while the former plays a more active role in inhibiting microbial invasion during mucosal-barrier disruption (15-17). Moreover, in addition to their antimicrobial properties (18, 19), both peptides have been shown to act as chemokines in recruiting lymphoid and myeloid cells from the bloodstream (20).Fusobacterium nucleatum, a ubiquitous Gram-negative bacterium of the human oral cavity, has been extensively studied for its properties of adhesion to other bacteria, an important feature in oral biofilm formation (21,22). In addition to its role in oral community architecture, we and others have shown that the cell wall of F. nucleatum induces hBD-2 expression in normal primary human oral epithelial cells (HOECs) (1,5,10,23).…”
mentioning
confidence: 99%